Safety evaluation on concomitant immunization with inactivated poliomyelitis vaccine produced from Sabin strains and other vaccines (from 2015 to 2020) - Yan Deng; Li Yi; Ying Li; Zhimei Zhao; Zhilei Zhong; Haoyu Shi; Jiarong Li; Yan Liang; Jingsi Yang (Human Vaccines & Immunotherapeutics, 2022)
Objective To evaluate the safety of concomitantly administering inactivated poliomyelitis vaccine produced from Sabin strains (sIPVs) with other vaccines. Methods A descriptive analysis was carried out on adverse events following immunization (AEFI) based on the administration of sIPV alone or concomitant with other vaccines (from 2015 to 2020) using data from the national AEFI surveillance system of China (CNAEFIS). All adverse reactions (ADRs) of the concomitant immunization were coded using a medical dictionary for regulatory activities (MedDRA) before comparison. Results The CNAEFIS reported a total of 9130 sIPV-related AEFI cases, including 6842 AEFI cases collected after immunization with sIPV alone and 2288 AEFI cases collected after immunization of sIPV concomitant with other vaccines. The combination of sIPV with diphtheria, tetanus and pertussis vaccine (DTaP) was correlated with the highest frequency of AEFI, which accounted for 53.50% of all 2288 AEFI cases. After MedDRA-based coding, the most frequent ADR was fever (70.18%), followed by erythema and swelling at the injection site (6.95%), induration at the injection site (3.85%), dermatitis allergy (3.56%) and urticaria (1.55%). A statistically significant difference (P < .001) was found between sIPV immunization and sIPV immunization concomitant with other vaccines for general reactions (95.36% and 93.22%, respectively) and abnormal reactions (4.64% and 6.78%, respectively). Conclusion No new safety signal is found for sIPV administered concomitantly, although its administration with other vaccines may increase the occurrence of abnormal reactions. Vaccine manufacturers should focus on the safety of administering sIPV with DTaP and carry out relevant clinical studies when necessary.